Filtered GBIF derived dataset for food species in the brown bear (Ursus arctos) trophic database - Pablo_m_lucas (The Global Biodiversity Information Facility, 2024)
We reviewed 47 studies of brown bear diet in Europe by searching in SCI Journals, master’s and PhD theses, and grey literature. We obtained a list of 276 species in the brown bear diet in Europe and Turkey. We used the R package rgbif to download occurrences of each food species from the Global Biodiversity Information Facility (GBIF). We selected occurrences of food species, with an uncertainty of <1 km2, in Europe, North Africa and the Middle East for the period 1989–2018.